2021
DOI: 10.3390/ijms23010253
|View full text |Cite
|
Sign up to set email alerts
|

Histone Modifications and Their Targeting in Lymphoid Malignancies

Abstract: In a wide range of lymphoid neoplasms, the process of malignant transformation is associated with somatic mutations in B cells that affect the epigenetic machinery. Consequential alterations in histone modifications contribute to disease-specific changes in the transcriptional program. Affected genes commonly play important roles in cell cycle regulation, apoptosis-inducing signal transduction, and DNA damage response, thus facilitating the emergence of malignant traits that impair immune surveillance and favo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 222 publications
(260 reference statements)
0
7
0
Order By: Relevance
“…Regarding tumour development and progression, several histone modifications have been found. For example, functional dysregulation of histone acetyltransferases has been associated with cancer development, including B-cell [45,46] and T-cell lymphomas [47,48]. In humans, histone modifier gene mutations have been associated with inferior progression-free survival time in patients with T-cell lymphomas [48], and it has been demonstrated that HDAC regulates the expression of BCL6, involved in cell survival and/or differentiation in B-cell lymphoma [49], and HDAC inhibitors have been tried as therapy in humans [50][51][52].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Regarding tumour development and progression, several histone modifications have been found. For example, functional dysregulation of histone acetyltransferases has been associated with cancer development, including B-cell [45,46] and T-cell lymphomas [47,48]. In humans, histone modifier gene mutations have been associated with inferior progression-free survival time in patients with T-cell lymphomas [48], and it has been demonstrated that HDAC regulates the expression of BCL6, involved in cell survival and/or differentiation in B-cell lymphoma [49], and HDAC inhibitors have been tried as therapy in humans [50][51][52].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…These genes play crucial roles in cell proliferation and differentiation, and their mutations can contribute to lymphomagenesis. Additionally, similar patterns of epigenetic modifications, such as DNA methylation and histone modifications, have been observed in both types of lymphoma, underscoring their significant roles in these diseases ( 85 , 86 ). Lastly, there is indeed a convergence in the dysregulation of signaling pathways in MZL and DLBCL.…”
Section: Discussionmentioning
confidence: 66%
“…Aberrant EZH2 expression has been associated with various human cancers. For example, the overexpression of EZH2 has been detected in prostate, breast, and other cancers, suggesting that it might serve as a prognostic marker for cancers ( 43 , 81 ). Further, wild-type and mutant EZH2 cooperatively regulate and maintain the hypertrimethylation of H3K27, which inhibits the proliferation of lymphoma cells by abnormally silencing PCR2-target genes ( 47 ).…”
Section: Histone Methylation As An Anticancer Targetmentioning
confidence: 99%